Financial integration and growth outcomes in Africa: Experience of the trade blocs - Ibrahim A. Adekunle; Abayomi Toyin Onanuga; Ibrahim Abidemi Odusanya (African Governance and Development Institute (AGDI), 2021)
In this study, we examine the benefits of financial integrations in four of Africa regional trade blocs: COMESA, ECCAS, CEN-SAD and ECOWAS. We regress de-jure and de-facto indices of financial integration on growth outcome using the dynamic system generalised method of moment and pooled mean group estimation procedure. Findings revealed that total foreign asset and liabilities and foreign liabilities as a percentage of GDP are inversely related to growth outcomes in COMESA. In CEN-SAD, we found that foreign liabilities as a percentage of GDP hurts growth. In ECCAS, growth-financial integration relationship showed that foreign liabilities as a percentage of GDP inhibit real per capita GDP in the long run. In ECOWAS, foreign liabilities as a percentage of GDP is inversely related to real per capita GDP in the long run. Policy implications of our findings were discussed.
Keywords: F36; F43; O47; 330; Financial Integration; Economic Growth; system GMM; Pooled Mean Group; Regional Trade Bloc; Africa